2020
DOI: 10.3390/vaccines8040718
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polymers for the Delivery of the Ebola DNA Vaccine Encoding Artificial T-Cell Immunogen

Abstract: Background: According to current data, an effective Ebola virus vaccine should induce both humoral and T-cell immunity. In this work, we focused our efforts on methods for delivering artificial T-cell immunogen in the form of a DNA vaccine, using generation 4 polyamidoamine dendrimers (PAMAM G4) and a polyglucin:spermidine conjugate (PG). Methods: Optimal conditions were selected for obtaining complexes of previously developed DNA vaccines with cationic polymers. The sizes, mobility and surface charge of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
0
28
0
1
Order By: Relevance
“…To package mRNA, a polycationic polymer polyglucin:spermidine conjugate (PGS) was used. The choice of PGS was due to the fact that we had previously successfully tested it for the delivery of DNA vaccines [21][22][23]39]. PGS was included in the candidate HIV-1 vaccine CombiHIVvac, which passed the first phase of clinical trials [40,41] which demonstrated the safety of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To package mRNA, a polycationic polymer polyglucin:spermidine conjugate (PGS) was used. The choice of PGS was due to the fact that we had previously successfully tested it for the delivery of DNA vaccines [21][22][23]39]. PGS was included in the candidate HIV-1 vaccine CombiHIVvac, which passed the first phase of clinical trials [40,41] which demonstrated the safety of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of polysaccharide conjugate was performed as described earlier in [21][22][23]. Briefly, polyglucin (dextran 40,000) was incubated with sodium periodate (40 molecules of sodium periodate per 1 molecule of dextran) for one hour and desalted by gel filtration on Sephadex G-25 in 50 mM carbonate buffer (pH 8.6).…”
Section: Preparation Of the Polyglucin:spermidine Conjugatementioning
confidence: 99%
“…ICS was performed according to a standard protocol as previously described [ 24 ]. Briefly, splenocytes isolated from mice 2 × 10 6 cells/well were plated in 24-well plates and stimulated with mix of VACV-specific peptides (SPYAAGYDL, SPGAAGYDL, VGPSNSPTF, KYGRLFNEI, GFIRSLQTI, and KYMWCYSQV) or with PMA (phorbol myristate acetate, 30 ng/mL) and ionomycin (1 µg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The dendrimers delivered artificial polyepitope T-cell immunogens in the form of a DNA. Due to relatively low immunogenicity, this approach needs more research [ 63 ].…”
Section: Application Of Dendrimers In Treatment Of Infectious Diseasesmentioning
confidence: 99%